TFL1-like genes in Vigna unguiculata (L.) Walp. with different growth habit types - E. A. Krylova; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
Background. Vigna unguiculata (L.) Walp. is among important legume crops. Agricultural producers prefer cultivars suitable for mechanized cultivation, with a determinate growth habit type. Plant architectonics depends on the functioning of the apical meristem, while the transition to the reproductive stage is controlled by a set of genes, including the TFL1 gene. Analyzing the genes responsible for the growth habit type is relevant for more efficient and rapid development of high-tech cultivars. Materials and methods. Using the Sanger DNA sequencing method, the primary structure of TFL1-like genes was studied in six cowpea accessions with different growth habit types and architectonics.Results. Promoter regions and coding parts of TFL1-like genes (VuTFL1.1, VuTFL1.2, VuATC, and VuBFT) were sequenced and analyzed. Information about the genes is available in the NCBI nucleotide sequence database. A comparative study showed that there were no exon differences between different genotypes. Rearrangements were found in the introns and the promoter region, but no relationship was traced between these rearrangements and the phenotype in terms of growth habit types or architectonics.Conclusion. The next step towards understanding the role of TFL1-like genes requires obtaining knockout lines based on these genes and studying their phenotype. Meanwhile, the results of this analysis call for a need to consider a wider range of cowpea genes potentially associated with the variability of stem growth habit types and plant architectonics.